2004
DOI: 10.1007/s00253-003-1529-7
|View full text |Cite
|
Sign up to set email alerts
|

CYP175A1 from Thermus thermophilus HB27, the first �-carotene hydroxylase of the P450 superfamily

Abstract: The biological function of thermostable P450 monooxygenase CYP175A1 from Thermus thermophilus HB27 was studied by functional complementation in Escherichia coli. The gene product of CYP175A1 added hydroxyl groups to both beta rings of beta-carotene to form zeaxanthin (beta,beta-carotene-3,3'-diol) in E. coli, which produces beta-carotene due to the Erwinia uredovora carotenoid biosynthesis genes. In addition, spectroscopic methods revealed that E. coli carrying CYP175A1 and the cDNA of the Haematococcus pluvia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 16 publications
0
35
0
2
Order By: Relevance
“…The location of this single P450 gene on the thermophile's megaplasmid suggests that the gene may have been acquired through horizontal transfer and perhaps conferred some advantage to heat stress. The bacterial gene encodes a 44 kDa (9.72 pI) enzyme in comparison to the predicted mature 66 kDa (5.44 pI) plant Clan A enzyme [72,73], though they share 21% similar residues and cluster in a neighbor-joining tree [74]. While the plant and bacterial enzymes are sufficiently different, and perhaps cases of convergent evolution, they both functioned in E. coli.…”
Section: What Is the Structural Basis For Enzyme Specificity?mentioning
confidence: 99%
“…The location of this single P450 gene on the thermophile's megaplasmid suggests that the gene may have been acquired through horizontal transfer and perhaps conferred some advantage to heat stress. The bacterial gene encodes a 44 kDa (9.72 pI) enzyme in comparison to the predicted mature 66 kDa (5.44 pI) plant Clan A enzyme [72,73], though they share 21% similar residues and cluster in a neighbor-joining tree [74]. While the plant and bacterial enzymes are sufficiently different, and perhaps cases of convergent evolution, they both functioned in E. coli.…”
Section: What Is the Structural Basis For Enzyme Specificity?mentioning
confidence: 99%
“…Genes for both types of enzyme may have been acquired from carotenoid-producing bacteria. Plant CrtZ-type ␤-carotene hydroxylases are similar in amino acid sequence to certain bacterial and archaeal enzymes that serve the same function, and the cytochrome P450 class of carotenoid ␤-ring hydroxylases also has representatives in carotenoid-producing bacteria (6).…”
mentioning
confidence: 99%
“…6,2007 CAROTENOID BIOSYNTHESIS IN CYANIDIOSCHYZON MEROLAE 543 (41). Whether this approach is applicable to genes of the plastid genome, and to crtR in particular, is not known.…”
mentioning
confidence: 99%
“…The carotenoid oxygenases identified to date are not heminic enzymes since the recent X-ray structure analysis of a carotenoid oxygenase showed the presence of 4 histidine residues chelating the iron center [60]. However, it was recently shown that carotenoid hydroxylation is catalyzed by CYP 450 in bacteria [69] and in plants [70,71]. A well-developed and elegant porphyrin model of a catalytic system has been used to mimic the central cleavage of carotenoids [72].…”
Section: Carail and C Caris-veyratmentioning
confidence: 99%